2022
DOI: 10.25165/j.ijabe.20221504.7114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant activity of blueberry ethanol extracts under microwave extraction

Abstract: Blueberry extract contains diversiform monomers of anthocyanins, whose antioxidant activity determines the functionality of anthocyanidins and the efficacy of extraction technology. The evaluation of the antioxidant activity of anthocyanidins of blueberry ethanol extracts (BEE) was investigated by considering the monomers' identification and thermal degradation in microwave-assisted extraction (MAE). Thirteen monomers of anthocyanins were identified from the extracts of blueberry under MAE, where the highest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For instance, Schmidt (2001) showed that beehives marked with synthetic Nasonov pheromone were more attractive to honeybees and Mayer, Britt et al, 1989, Mayer, Johansen et al (1989) found that NGP increased honeybee visitation and fruit set in apple, cherry and pear in the USA. In China, the application of NGP lures increased the honeybee visitation frequency and fruit set in blueberry (Liu et al, 2016) and sweet cheery (Wang et al, 2021). However, in orchards without beehives pear flower visitation rates were low, despite the 27.6‐fold higher flower visitation rates in trees with NGP lures than without NGP lures (1.38 ± 0.96 vs. 0.05 ± 0.05 visits per 40 min).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Schmidt (2001) showed that beehives marked with synthetic Nasonov pheromone were more attractive to honeybees and Mayer, Britt et al, 1989, Mayer, Johansen et al (1989) found that NGP increased honeybee visitation and fruit set in apple, cherry and pear in the USA. In China, the application of NGP lures increased the honeybee visitation frequency and fruit set in blueberry (Liu et al, 2016) and sweet cheery (Wang et al, 2021). However, in orchards without beehives pear flower visitation rates were low, despite the 27.6‐fold higher flower visitation rates in trees with NGP lures than without NGP lures (1.38 ± 0.96 vs. 0.05 ± 0.05 visits per 40 min).…”
Section: Discussionmentioning
confidence: 99%
“…Blueberry extract, rich in anthocyanins and antioxidants, has demonstrated potential neuroprotective and IOP-lowering properties in pre-clinical studies. [15][16][17] In this research, we explore the development and evaluation of an in situ gel formulation containing blueberry extract as a novel approach for glaucoma management.…”
Section: Original Articlementioning
confidence: 99%